Power, law, and maritime order in the South China Sea - Tran, Truong Thuy; Le, Thuy Trang (Lexington Books, 2015)
With contributions from some of the most well-known scholars and knowledgeable insiders in the field of South China Sea studies, this book offers an array of views from international relations and legal perspectives that will help enrich the ongoing global discussion on conflict management and resolution in the South China Sea.